2021
DOI: 10.3390/microorganisms9061204
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient Anthrax Lethal Toxin Neutralization Is Associated with Antibody Subclass and Domain Specificity in the Plasma of Anthrax-Vaccinated Individuals

Abstract: Anthrax vaccine adsorbed (AVA) is a significant line of defense against bioterrorist attack from Bacillus anthracis spores. However, in a subset of individuals, this vaccine may produce a suboptimal quantity of anti-protective antigen (PA), antibodies that are poorly neutralizing, and/or antibody titers that wane over time, necessitating annual boosters. To study individuals with such poor responses, we examine the properties of anti-PA in a subset of vaccinated individuals that make significant quantities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In that context, it is reassuring that there is a highly positive correlation between anti-PA IgG titers and TNA activity [ 28 ]. Although this holds overall for combined, aggregate data, there is a differentiation among IgG classes and among the PA domains against which the antibodies are directed [ 29 ]. More specifically, it was found that (a) anti-PA antibodies with a high IgG4/IgG1 ratio are less potent on Lethal Toxin-Neutralizing Activity (LTNA), and (b) IgG1 antibodies directed against epitopes from PA domain 4 are more potent on LTNA [ 29 ].…”
Section: Antibodies To Anthrax Proteins and Anthrax Toxinsmentioning
confidence: 99%
See 4 more Smart Citations
“…In that context, it is reassuring that there is a highly positive correlation between anti-PA IgG titers and TNA activity [ 28 ]. Although this holds overall for combined, aggregate data, there is a differentiation among IgG classes and among the PA domains against which the antibodies are directed [ 29 ]. More specifically, it was found that (a) anti-PA antibodies with a high IgG4/IgG1 ratio are less potent on Lethal Toxin-Neutralizing Activity (LTNA), and (b) IgG1 antibodies directed against epitopes from PA domain 4 are more potent on LTNA [ 29 ].…”
Section: Antibodies To Anthrax Proteins and Anthrax Toxinsmentioning
confidence: 99%
“…Although this holds overall for combined, aggregate data, there is a differentiation among IgG classes and among the PA domains against which the antibodies are directed [ 29 ]. More specifically, it was found that (a) anti-PA antibodies with a high IgG4/IgG1 ratio are less potent on Lethal Toxin-Neutralizing Activity (LTNA), and (b) IgG1 antibodies directed against epitopes from PA domain 4 are more potent on LTNA [ 29 ]. These factors would naturally affect the ultimate protection of the vaccinee against anthrax exposure.…”
Section: Antibodies To Anthrax Proteins and Anthrax Toxinsmentioning
confidence: 99%
See 3 more Smart Citations